If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9y + 5) = (6y + -2) Reorder the terms: (5 + 9y) = (6y + -2) Remove parenthesis around (5 + 9y) 5 + 9y = (6y + -2) Reorder the terms: 5 + 9y = (-2 + 6y) Remove parenthesis around (-2 + 6y) 5 + 9y = -2 + 6y Solving 5 + 9y = -2 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 5 + 9y + -6y = -2 + 6y + -6y Combine like terms: 9y + -6y = 3y 5 + 3y = -2 + 6y + -6y Combine like terms: 6y + -6y = 0 5 + 3y = -2 + 0 5 + 3y = -2 Add '-5' to each side of the equation. 5 + -5 + 3y = -2 + -5 Combine like terms: 5 + -5 = 0 0 + 3y = -2 + -5 3y = -2 + -5 Combine like terms: -2 + -5 = -7 3y = -7 Divide each side by '3'. y = -2.333333333 Simplifying y = -2.333333333
| 4v^2-64v+28=0 | | (-2a-7)(b-2)= | | 2y^2+92y=0 | | 2-a+3a-4-5+2a-a= | | sin((10pi/2))-0 | | 98w^2-8=0 | | v*3.2=19 | | (2x-1)-(5x-6)=0 | | 3f^2+72f=0 | | 7.2=u*1.5 | | a+2b-b-3a+4a-2b+1= | | 3u^2+11u-14=0 | | a+b+c+a+b+c= | | 104+9x=128+6x | | 2x^(7/3)-22=0 | | x-0.9x-2=6.5(x+5.6) | | y-4/5=3 | | -3(5x-6)=-3x | | 15y-45=38y | | -3(5x-6)=-3 | | 3(x+4)=8(4-3x)+27x | | 5x-8=-4x+10 | | -5(x-9)=-7(x-7) | | -2.3x-5.1=1.7x-1.1 | | 8x^2+3x=1 | | 6x-11=-5x+11 | | h-e=x | | 5/4=600/x | | x*x*x=x*x+12*x | | 1/3x5/9 | | x*x*x=x*x+12*c | | 3(x-2)=-4(x+2) |